Efektifitas Pasal 39 Ayat 1 Undang-Undang Perkawinan Tentang Perceraian Pengadilan Pada Masyarakat Desa Apitaik - Linda Yulianti; Any Suryani Hamzah (Fakultas Hukum Universitas Mataram, 2022)
This study describes the practice of divorce in Apitaik Village Community, and observes the effectivity of Article 39 paragraph (1) of the Marriage Law, as well as identifies factors affecting the divorce practice. This study is a descriptive normative-empirical one. Data in this study consists on interview as primary ones, and laws and regulations as secondary ones. Results of this study show that the divorce practice in Apitaik Village Community is still verbally completed by husbands. Likewise, the reconciliation is also verbally completed. Implying from these practices, the provision of Article 39 paragraph (1) is considered unfeasible. This is due to several factors. The first and the second are that the community assumes that divorcing officially is time consuming and bothering. Moreover, they consider completing the divorce verbally is more economical than the official ones. The other is the lack of legal awareness of locals. In addition, distant Religious Court office may lead to locals’ reluctance to officially proceed their divorce.